Leukocyte Telomere Length in Young Adults Born Preterm: Support for Accelerated Biological Ageing. - Carolina C J Smeets; Veryan Codd; Nilesh J Samani; Anita C S Hokken-Koelega (PLoS ONE)
Background Subjects born preterm have an increased risk for age-associated diseases, such as cardiovascular disease in later life, but the underlying causes are largely unknown. Shorter leukocyte telomere length (LTL), a marker of biological age, is associated with increased risk of cardiovascular disease. Objectives To compare LTL between subjects born preterm and at term and to assess if LTL is associated with other putative cardiovascular risk factors at young adult age. Methods We measured mean LTL in 470 young adults. LTL was measured using a quantitative PCR assay and expressed as T/S ratio. We analyzed the influence of gestational age on LTL and compared LTL between subjects born preterm (n = 186) and at term (n = 284). Additionally, we analyzed the correlation between LTL and potential risk factors of cardiovascular disease. Results Gestational age was positively associated with LTL (r = 0.11, p = 0.02). Subjects born preterm had shorter LTL (mean (SD) T/S ratio = 3.12 (0.44)) than subjects born at term (mean (SD) T/S ratio = 3.25 (0.46)), p = 0.003). The difference remained significant after adjustment for gender and size at birth (p = 0.001). There was no association of LTL with any one of the putative risk factors analyzed. Conclusions Young adults born preterm have shorter LTL than young adults born at term. Although we found no correlation between LTL and risk for CVD at this young adult age, this biological ageing indicator may contribute to CVD and other adult onset diseases at a later age in those born preterm.